The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1108/09526860910953502
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of physicians in Russia

Abstract: There is scant empirical data on the job satisfaction of physicians in Russia. This paper found that job characteristic variables such as clinical autonomy, resources, time, and administration moderate physician satisfaction relationships in Russia, just as they do in the West.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
(25 reference statements)
0
11
0
3
Order By: Relevance
“…There is a high proportion of female physicians in the primary public health sector, and among general physicians. In the survey on job satisfaction of physicians in Russia, there were 87.2% of female respondents in polyclinics and 67.3% of female respondents in hospitals [21]. On the other hand, in the survey of job satisfaction of physicians at a university center in Germany, male respondents consisted 65.5% [22].…”
Section: Discussionmentioning
confidence: 98%
“…There is a high proportion of female physicians in the primary public health sector, and among general physicians. In the survey on job satisfaction of physicians in Russia, there were 87.2% of female respondents in polyclinics and 67.3% of female respondents in hospitals [21]. On the other hand, in the survey of job satisfaction of physicians at a university center in Germany, male respondents consisted 65.5% [22].…”
Section: Discussionmentioning
confidence: 98%
“…In terms of career satisfaction among Russian physicians, one study found that male physicians were more satisfied with their careers than female physicians. 44 In Hungary, while the proportion of female physicians has steadily increased from 30% in 1970 to 52% in 2012, women physicians continue to face challenging cultural and professional expectations and lack of workplace support. 45 Only 6% of female workers work part time, which is the lowest proportion in the European Union, and 3% of female physicians work part time.…”
Section: Case 3: Eastern Europe and Russiamentioning
confidence: 99%
“…Висок је проценат жена лекара у државним здравственим установама које обезбеђују примарну здравствену заштиту становништву и међу лекарима опште медицине. У Русији, у поликлиничкој здравственој заштити ради 87,2% лекара женског пола, док у болницама ради 67,3% (5). У Финској, у болничкој здравственој заштити ради 44% жена лекара са специјализацијом (23).…”
Section: карактеристике здравствених радникаunclassified
“…Последњих година спроведене су бројне студије које су се бавиле испитивањем различитих фактора утицаја на професионално задовољство лекара, сестара, као и њихове међусобне односе, а у циљу идентификовања фактора који превенирају незадовољство запослених и обезбеђују жељени ниво професионалног задовољства (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Познато је да се повећањем нивоа задовољства постиже већа продуктивност и ефикасност запослених, као и виши квалитет услуга (15).…”
unclassified